East Meets West: A Cross‐Cultural Comparison of Charismatic Leadership Among Canadian and Iranian Executives - Javidan, Mansour; Carl, Dale E. (Journal of Management Studies, 2004)
ABSTRACT This study first develops an empirically based Western charismatic leadership profile. Using confirmatory factor analysis, the profile is compared with a profile of Iranian managers. The results demonstrate that despite major cultural differences in the two countries, there are core similarities in the profiles across the two cultures. The Canadian charismatic profile of vision, tenacity, intellectual challenge, self‐sacrifice, and eloquence is substantially confirmed within the Iranian sample. But we also show that Iranian managers’ ratings are significantly lower than those of the Canadian managers, indicating potentially different behavioural manifestations. The paper speculates that while the differences are probably due to cultural differences, the similarities may be due to universal intrinsic human desire for morality, autonomy, and achievement.